THE MODEL OF OUTSOURCING WORK RELATIONSHIP IN GLOBALIZATION ERA OF LABOR MARKET BASED ON PANCASILA - Mashari Mashari (UNTAG Law Review, 2018)
The outsourcing relationship model in the globalization of the labor market based on Pancasila is still reaping controversy among workers and employers. The issue of outsourcing employment relationships in the globalization era of the labor market is a common need among workers, employers and governments. In the implementation of this outsourced employment relationships lead to inconsistency in the element of the employment relationship itself, because workers get orders from employers, whereas employment agreements are made between workers and the Worker Service Company. This inconsistency leads to industrial disputes between outsourced workers and employers. The concept of outsourcing work relations in the era of labor market globalization is a product of liberalism adopted by the Indonesian people when entrepreneurs feel overwhelmed by high labor costs and obliges to provide severance pay, rewards of employment and compensation as regulated in Law Number 13 2003. The implementation of work relations between workers, employers and the government must be in accordance with the souls contained in the precepts of Pancasila, meaning that all forms of behavior of all subjects involved in the process must be based on the noble values of Pancasila as a whole. Outsourcing employment relationship model in the era of labor market globalization based on Pancasila has not run as expected, there are still many problems in the unfinished work of outsourcing industry. The outsourcing work relationship based on Pancasila should make employers and workers no longer across but have the same goal to achieve profit.